Online interpersonal relationship strategies between same gender among Malaysian chatters - Bolong, Jusang; Waheed, Moniza (Faculty of Modern Languages and Communication, University of Putra, 2013)
Strategies utilised by users of the Internet Relay Chat (IRC) will determine the level of their interpersonal relationship in Computer Mediated Communication (CMC). However, strategies for establishing relationships between the same gender differ from one another. Therefore, this study intends to answer the question of whether or not differences exist in the utilisation of strategies in the form of online interpersonal relationships for chat partners of the same gender. This study undertakes a quantitative approach. However, in-depth interviews are used to obtain the strategies that are used to build interpersonal relations through CMC by IRC users. All the strategies are modified to create questions in the research instrument in order to conduct a study through a survey method. A multi-regression analysis was conducted to analyse the data. The results show that male IRC users interact with one another by using only one strategy, which is the strategy to create similar values/ understanding of the meaning of emoticons. When female IRC users interact with one another, they use three main strategies; strategy of relationship continuity through e-mail, strategy to create similar values/ understanding of the meaning of emoticons, and strategy of satisfaction fulfilment of the chat buddy. The results of this study provide implications toward face-to-face interpersonal communication-related theories and their applications in the context of CMC.